Do Students Use the Three Levels of Representation-based Visual Media Effectively in Constructivism Learning? A Focus on Battery Concept - Putri*, Ananda Hafizhah; Suhandi, Andi; Samsudin, Achmad; Setiawan, Agus; Cotu, Bayram; Supriyadi, Supriyadi (Universitas Syiah Kuala, 2025)
With advances in technology, learning physics must be supported by the use of media that are capable of representing physics concepts in macroscopic, symbolic, and microscopic. This study aims to explore students interpretation and response toward the three levels of representation-based visual media and its implementation in constructivist teaching sequence (CTS) about battery function in electrical circuit. The three levels of representation-based visual media consist of phenomena video, dynamic analogies, and microscopic models. The study involved 25 twelfth-grade students (14 female and 11 male) from a high school in Bandung, Indonesia. The content interpretation of visual media was qualitatively analysed through student worksheets. After the completing lesson, an attitude scale was administered to collect students response toward the three levels of representation-based visual media and its implementation. The findings of this study can assist physics teachers and researchers to develop innovative pedagogies that consider students interpretation ability to promote conceptual change learning